Sports culture among Malaysians: challenges and way forward - Elumalai, Gunathevan; Aman, Mohd Salleh; Zamri, Nur Najmin Naja; Ponnusamy, Vellapandian; Mamat, Shariffah; Sharif, Shamshuritawati; Ismail, Hashbullah; Arshad, Mohd Mursyid; Suradi, Nur Riza; Imran, Farrah Hani (Horizon Research Publishing, 2024)
Sports culture can be defined as a positive value attitude of an individual to sport. These values act for the individual as social ideals, senses, symbols, norms, and samples of behavior that regulate the entire activity and social relations in a sports sphere. The Institute for Youth Research Malaysia (IYRES) initiated to determine the nation's sports culture since 2018. The latest research on the Malaysian Sports Index conducted in 2022, among 3735 respondents from various backgrounds according to age group, gender, ethnicity, and location using a self-designed questionnaire by IYRES with two domains and five indicators. The first domain is participation with activeness as the indicator. The second domain is sporting spirit with four indicators namely Voluntarism, Dedication, Expenditure and Contribution. Each and every indicator contributes towards Malaysian sports culture index based on the Index score scale created by experts from IYRES. The descriptive analysis showed Malaysian Sports Culture Index 2022 (MSCI’22) still in the moderate level with the score (52.0). The independent sample t-test showed there is significant difference by gender, with male (M= 59.06; SD=33.83) and female (M= 44.69; SD=32.90); p=0.000. Analysis by location also indicated that there is a significant difference in sports culture between urban and rural populations, with urban (M= 51.13; SD=34.19) and rural area (M= 54.78; SD=33.74); p=0.009. One-way ANOVA test to determine the sports culture based on ethnicity showed there were significant differences by ethnic group (p=0.000). The age group also showed a significant difference (p=.0.000) in sports culture among Malaysians. In conclusion, this research indicates that behavioral changes are needed among the Malaysian population to truly embed sports as a cultural element in their lives. Such changes cannot be expected to transpire immediately. To foster this transformation, raising awareness and providing accessible facilities for regular sports, exercise, and recreational activities are vital responsibilities for stakeholders because sports as a cultural can effectively enhance healthy lifestyles.